Hydrogels with Dual Thermoresponsive Mechanical Performance. Issue 17 (18th July 2017) - Guo, Hui; Mussault, Cécile; Marcellan, Alba; Hourdet, Dominique; Sanson, Nicolas
Abstract : Original chemical hydrogels combining antagonistic upper critical solution temperature and lower critical solution temperature polymers are elaborated via free radical polymerization. Rheological and mechanical experiments performed under isochoric conditions show a thermoinduced reinforcement both at low and high temperatures induced by the formation of phase‐separated polymer domains acting as organic reinforcing filler. Abstract : Dual thermoresponsive chemical hydrogels, combining poly( N ‐isopropylacrylamide) side‐chains within a poly( N ‐acryloylglycinamide) network, are designed following a simple and versatile procedure. These hydrogels exhibit two phase transitions both at low (upper critical solution temperature) and high (lower critical solution temperature) temperatures, thereby modifying their swelling, rheological, and mechanical properties. These novel thermo‐schizophrenic hydrogels pave the way for the development of thermotoughening wet materials in a broad range of temperatures.